Experiences of people with disabilities during their rehabilitation process: Grounded Theory - Simone Nunes Pereira; Miriam Fernanda Sanches Alarcon; Jaqueline Dias do Nascimento Selleti; Maria José Sanches Marin (Universidade Federal do Ceará, 2023)
Objective: to construct a theoretical model that can represent the experience of people with disabilities during the physical rehabilitation process. Methods: qualitative research, based on the theoretical framework of Grounded Theory. We interviewed 28 participants in three sample groups, using a theoretical sampling and data circularity to analyze initial, focused, and theoretical codings. Results: the phenomenon "Experiencing the process of rehabilitation" was formed by 66 conceptual codes. Its conditions were the categories: "Coping with the new condition", "Experiencing the challenge of rehabilitation". Action-interaction: "Finding motivation for rehabilitation"; consequence: "Adapting to the condition". Conclusion: the theoretical model highlights the need to cope with the disability, leading the individual to learn how to deal with challenges and to recognize the gradual and challenging nature of rehabilitation. Contributions to practice: the theoretical model is innovative for explaining the rehabilitation process in people with disabilities, highlighting the importance of facing the new condition, finding motivation, and adapting. The crucial role of the health team also stands out, as do the relevance of getting in touch with others who have been through the same process. The application of this model is expected to increase rehabilitation efficiency, culminating in higher quality of life for patients.